Exact sequences of graphs - Abbasi, A.; Ramin, A. (Algebra and Discrete Mathematics, 2019)
In this paper, exact sequences of graphs are defined and investigated. Considering some functors on the category of graphs, we study some conditions to determine exactness of functors.